Genomic surveillance of Pseudomonas aeruginosa in the Philippines, 2013-2014 - Chilam, Jeremiah; Argimon, Silvia; Limas, Marilyn T.; Masim, Melissa L.; Gayeta, June M.; Lagrada, Marietta L.; Olorosa, Agnettah M.; Cohen, Victoria; Hernandez, Lara T.; Jeffrey, Benjamin; Abudahab, Khalil; Hufano, Charmian M.; et al. (Western Pacific Surveillance and Response, 2021)
Pseudomonas aeruginosa is an opportunistic pathogen that often causes nosocomial infections resistant to treatment. Rates of antimicrobial resistance (AMR) are increasing, as are rates of multidrug-resistant (MDR) and possible extensively drug-resistant (XDR) infections. Our objective was to characterize the molecular epidemiology and AMR mechanisms of this pathogen. We sequenced the whole genome for each of 176 P. aeruginosa isolates collected in the Philippines in 2013-2014; derived the multilocus sequence type (MLST), presence of AMR determinants and relatedness between isolates; and determined concordance between phenotypic and genotypic resistance. Carbapenem resistance was associated with loss of function of the OprD porin and acquisition of the metallo-beta-lactamase (MBL) gene bla VIM. Concordance between phenotypic and genotypic resistance was 93.27% overall for six antibiotics in three classes, but varied among aminoglycosides. The population of P. aeruginosa was diverse, with clonal expansions of XDR genomes belonging to MLSTs ST235, ST244, ST309 and ST773. We found evidence of persistence or reintroduction of the predominant clone ST235 in one hospital, and of transfer between hospitals. Most of the ST235 genomes formed a distinct lineage from global genomes, thus raising the possibility that they may be unique to the Philippines. In addition, long-read sequencing of one representative XDR ST235 isolate identified an integron carrying multiple resistance genes (including bla VIM-2), with differences in gene composition and synteny from the P. aeruginosa class 1 integrons described previously. The survey bridges the gap in genomic data from the Western Pacific Region and will be useful for ongoing surveillance; it also highlights the importance of curtailing the spread of ST235 within the Philippines.